Development of a micro-compressed air energy storage system model based on experiments. (15th April 2020) - Chen, Shang; Arabkoohsar, Ahmad; Zhu, Tong; Nielsen, Mads Pagh
Abstract: Compressed air energy storage system is a promising electricity storage technology. There are several simplified thermodynamic models for performance assessment of compressed air energy storage systems that do not provide an exact picture of the system performance. In this work, a modeling methodology is proposed for developing the model of a compressed air energy storage system. The models of individual components are gathered to constitute the system overall model. Reliable models of the components in different configurations ranging from single-to multi-stage designs are presented. These created models are validated with a sort of tests on a lab-scale setup, observing mean-absolute-percentage-errors of smaller than 8% in the worst case. The experimental results and models show that the output performance of the expander and the overall efficiency of the system vary from different configurations. With the development of the model derived from the experiment, the optimal condition is suggested. The increase in the number of stages of the expanders leads to a significant jump in the overall efficiency of the system. The efficiency of the designed experimental setup in different conditions ranges from 13% to 25%, and the optimal system efficiency will increase to 60% for a triple-stage system. Highlights: Experimental tests of a micro-CAES system are carried out. A single-stage micro-CAES system model is derived and validated with the tests. The efficiency of the single-to multi-stage CAES system are investigated. The efficiency will increase to 60% of a triple-stage system from 25% of a single-stage system.